An Economic Development Architecture for New Orleans - McCarthy, Kevin F. (RAND Corporation, 2008)
In response to the current situation in New Orleans in the aftermath of Hurricane Katrina, this report provides recommendations regarding effective organizational and strategic approaches to revitalizing the city's economy, identifies the best practices that other cities have used to foster economic development, describes how these practices might be applied to New Orleans, and considers historical trends and past development missteps.